Analisis Kombinasi Produk Dalam Pencapaian Laba Maksimal Dengan Linier Programming Pada Usaha Kue Khas Kutai Hj Fatmah Di Tenggarong - Feni Arifah Agustina; Raudatul Adawiyah; Setiati Setiati (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The problem in this study is that the typical Cake Business Hj Fatmah has never planned on the profits of the company or its finances, so that in this case the business owner only uses the estimation method to maximize the profit generated. Business owners never plan and take into account products that should be produced optimally so that the company considers the benefits obtained to be maximized.The main objective of this study is to find out the number of product combinations in a day at the Cake Business Hj Fatmah in Tenggarong to be able to achieve maximum profit by using a simplistic method.The results showed that Cake Business Hj Fatmah had the maximum benefit of 2 (two) product combinations, namely Kue Cincin and Roti Balok products while Elat Cow products could not provide maximum benefits. The optimal production of each product, namely Elat Sapi as many as 0 units, Kue Cincin as many as 1,250 units and Kue Balok as many as 500 units with the maximum profit achieved amounting to Rp.2,362,500.Keywords: Maximum Profit, Optimal Quantity